Peningkatan Hasil Belajar Matematika Melalui Alat Peraga Tangga Pintar Satuan Panjang pada Siswa Kelas V SDN Pranggang 3 - Rahma, Ade Meyra; Hima, Lina Rihatul (LP. Ma'arif Janggan Magetan, 2023)
The background to this research is the lack of student learning outcomes in class V mathematics subjects at SDN Pranggang 3. Class V students at SDN Pranggang 3 still experience difficulties when understanding length unit material. The factor that influences the lack of learning outcomes is that the learning process does not or does not involve students directly and is only explained by the teacher. The aim of this research is to determine students' understanding of length unit material by using a smart ladder teaching aid with the demonstration method. This research is classroom action research with a qualitative approach. The subjects of this research were fifth grade students at SDN Pranggang 3. Based on the results of interviews with students who obtained results above the KKM, they said that it was more fun if they could directly practice the material they were studying rather than just reading it. Meanwhile, students whose scores were below the KKM felt that they did not understand when multiplying or when dividing the questions that had been given. Mathematics lessons on length unit material using this smart ladder teaching aid can help elementary school students understand length unit material.